NEV TECHNOLOGIES IN THE RESTAURANT MARKET AS A RESULT OF THE FORMATION OF NEW CONSUMER HABITS AND LIKES (Development Service Industry Management, 2024)
To identify the strategies that will shape the restaurant industry in 2025 and beyond, internet search research and forecasting of leading restaurateurs was conducted and analyzed. Businesses should develop strategies in this direction with an awareness of their strengths and weaknesses. The COVID-19 pandemic has helped shape new behavioral habits, and now, in a post-pandemic world, the habit of ordering food is only getting stronger. Remote work, busy lifestyles, development and expansion of cities, growth in the specific weight of the urban population, etc. create a desire to save time, which leads to an increase in demand for convenient food delivery services. Born and raised around computers, game consoles, mp3 players, video cameras, cell phones and other digital toys, the younger generation naturally has the ability to use the Internet and Internet technologies. This feature has turned them into agents of change in the restaurant industry. They value convenience, so they prefer mobile apps and online food ordering platforms that offer quick and easy solutions. Due to the high demand for food delivery, restaurants are looking for economical commercial kitchens for food preparation. Restaurants need to redefine their purpose, move to completely new locations, where uninterrupted delivery is a priority, costs are minimized and profits are maximized, to densely populated areas with the highest number of delivery orders, to reach more customers online, to drive the growth of their restaurant and earning potential across the country. Virtual brands are one of the most talked about trends in hospitality. Over the past few years, online-only restaurants and ghost kitchens (or dark kitchens, cloud kitchens) have become commonplace on food delivery platforms around the world. In this context, this study aims to holistically assess the trends and forecasts in the restaurant industry for the increase of restaurant delivery and take-out services by applying cloud kitchen and virtual brand technologies, contribute to the literature and offer suggestions to relevant stakeholders.
Keywords: restaurant business; innovation; innovative development; innovative technologies; cloud technologies; innovation strategy